Yield and Quality in Main and Ratoon Crops of Grain Sorghum Under Different Nitrogen Rates and Planting Densities - Zhou, Yu; Huang, Juan; Li, Zebi; Wu, Yu; Zhang, Jijun; Zhang, Yaqin (Frontiers in Plant Science, 2022)
Ratooning is the cultivation practice of two harvests in one cropping season by producing a second crop from the original stubble, which could provide higher resource use efficiency and economic benefit compared with direct sown crops. Nitrogen (N) fertilizer and planting density (D) play a vital role in sorghum (Sorghum bicolor L.) production; however, limited information is available on the effects on yield and quality of the sorghum-ratoon system. To address this question, field experiments were conducted with three N treatments (120 kg N ha–1, N1; 180 kg N ha–1, N2; and 255 kg N ha–1, N3) and three D treatments (82,500 plant ha–1, D1; 105,000 plant ha–1, D2; and 127,500 plant ha–1, D3). The yield of the main crop was significantly higher than that of the ratoon crop. Increasing N could increase the yield and yield attributes of both main and ratoon crops, and the effect on the ratoon crop was greater than the main crop. With increasing D, the grain yield of both main and ratoon crops increased, though 1,000-grain weight and grain weight per ear decreased. The sorghum grain of the ratoon crop contained higher starch, protein, and tannin contents but lower fat content, indicating a better quality for liquor production. The quality traits were significantly affected by N and D, but the differences between treatments were smaller than that between the main and ratoon crop. Our results indicated that increasing the yield of ratoon crops could obtain a high yield and quality of the sorghum-ratoon system. It was recommended that 120 kg N ha–1 with 127,500 plant ha–1 for the main crop and a small amount of N be top-dressed in three new buds left on stubble in each hill for the ratoon crop.